Human Polymorphisms as Clinical Predictors in Leprosy - Ernesto Prado Montes de Oca (Journal of Tropical Medicine)
Genetic and serum markers in human host can predict leprosy susceptibility per se as well as be useful in classification and/or prediction of clinical variants and immunological responses in leprosy. Adequate and timely assessment of potential risks associated with these 38 host leprosy genes could diminish epidemiological burden and improve life quality of patients with this still prevalent mycobacterial disease.